Peramalan Jumlah Produksi Bawang Merah Provinsi Sumatera Barat Menggunakan Metode Triple Exponential Smoothing Tipe Brown - Rahmadani, Suci; Helma, Helma (UNIVERSITAS NEGERI PADANG, 2023)
Onion (Allium Ascalonicum L) is an important food ingredient that is widely used by the community and has a high market value. The increase in population in West Sumatra province every year has an impact on the need for onion. The amount of onion consumption is greater than the amount of production which causes unmet community needs for onion. This study aims to model onion production forecasts using the Brown Type Triple Exponential Smoothing technique and estimate onion production in West Sumatra province from based on the model that has been obtained. The smoothing parameter is , which is used in the quantitative forecasting process known as the Brown Type Triple Exponential Smoothing technique. After the data is analyzed and processed, it can be concluded that the results of the onion production forecast for 2023 to 2027 are 242.872,32 ton, 275.231,24 ton, 309.726 ton, 346.356,60 ton and 385.123,04 ton respectively.